2016
DOI: 10.1016/j.tiv.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of individual and combined mycotoxins in the THP-1 cell line

Abstract: Mycotoxins commonly contaminate food and may pose a risk for disease in humans and animals. As they frequently co-occur, mixed exposures often take place. Monocyte function, including differentiation into active macrophages, is a central part of the immune response. Here we studied effects of naturally co-occurring mycotoxins in grain on monocyte function, and effects of individual and combined exposure on the differentiation process from monocytes into macrophages. The THP-1 cell line was used as a model syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 66 publications
(90 reference statements)
7
63
0
1
Order By: Relevance
“…Cytotoxicity of AOH was only marginal in LPS-stimulated THP-1 derived macrophages, which is in line with previous findings (Fig. 1a–d) (Pahlke et al 2016; Solhaug et al 2015, 2016; Tiessen et al 2013). In recent times, more and more light was shed on the mycotoxin AOH and its ability to manipulate the rich network of multiple biological processes needed to strategically mount a defense response.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Cytotoxicity of AOH was only marginal in LPS-stimulated THP-1 derived macrophages, which is in line with previous findings (Fig. 1a–d) (Pahlke et al 2016; Solhaug et al 2015, 2016; Tiessen et al 2013). In recent times, more and more light was shed on the mycotoxin AOH and its ability to manipulate the rich network of multiple biological processes needed to strategically mount a defense response.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, AOH was reported to affect PMA-induced differentiation of THP-1 monocytes by reducing the expression of CD14 and CD11b, indicating a potentially reduced immune response. Indeed, in the same study, AOH (15 µM) diminished the immune response to LPS by alleviating secretion of the proinflammatory cytokine TNF-α (Solhaug et al 2016). Interestingly, in the present study we observed a substantial suppression of the LPS-induced NF-κB pathway activation after AOH (1–20 µM) exposure in differentiated THP-1 derived macrophages, which presumably may explain the previously observed immunosuppressive effects of AOH (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations